Pengembangan Ekowisata Bahari Pantai Karang Jahe Melalui Pembangunan Pariwisata Berkelanjutan - Triyono, Joko; Nugroho, Dwi Yoso (Metta : Jurnal Ilmu Multidisiplin, 2023)
The development of beach tourism has become an alternative for marine tourism. This research seeks to reveal this, as an added value based on the ecosystem of the coastal area of Karang Jahe Beach which has unique characteristics, biodiversity, human resources that have high productivity, the attractiveness of beautiful landscapes, and the availability of various services which are one of the main drivers of activities. Intensive development is being carried out at this tourist attraction. This research is descriptive qualitative with primary data sources coming from interviews with visitors and tourism managers. Apart from that, it is supported by observation results and documentation to crosscheck interview data. Secondary data sources come from scientific journals which can be accessed online. The data was analyzed using the 4A concept (Attractions, Accessibility, Amenities and Activities) to be used as an indicator that the object is worthy of being called sustainable tourism. The research results found evidence that supports the existence of the Karang Jahe Beach tourist attraction as part of sustainable tourism by fulfilling the supporting elements of attractions, accessibility, amenities and activities at the tourist attraction. The management of the Karang Jahe Beach tourist attraction deserves to be designated as marine ecotourism which is guided by the concept of sustainable tourism development. This can be seen from the community's participation in managing these tourist attractions while still paying attention to the natural ecosystem. Management is by developing tourism support facilities, natural beauty of beaches, and empowering management resources. In this way, tourism management has an economic impact while maintaining the natural ecosystem around the coast.